2017
DOI: 10.1155/2017/6942736
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Automated Test Column to Estimate Soil Hydraulic Characteristics in Unsaturated Porous Media

Abstract: The estimation of soil hydraulic properties in the vadose zone has some issues, such as accuracy, acquisition time, and cost. In this study, an inexpensive automated test column (ATC) was developed to characterize water flow in a homogeneous unsaturated porous medium by the simultaneous estimation of three hydraulic state variables: water content, matric potential, and water flow rates. The ATC includes five electrical resistance probes, two minitensiometers, and a drop counter, which were tested with infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…inaccuracy of computing S ) without performing an intensive field campaign, where infiltration tests are combined with measurements of hydraulic parameters in the laboratory and with 2D axisymmetric modelling of the flow below the infiltrometer ( Réfloch et al, 2017 ). It is also recommended that infiltration experiments be combined with innovative non-invasive methods such as Ground Penetrating Radar, which can show the wetting front evolution with time during water infiltration ( Iwasaki et al, 2016;Klenk et al, 2015;Leger et al, 2014aLeger et al, , b, 2015Salas-García et al, 2017 ). Réfloch et al (2017) also showed that monitoring the extension of the soil moisture stain around the infiltration ring with time is valuable for deriving the horizontal and vertical hydraulic parameters.…”
Section: Future Work and Recommendations To Improve Bestmentioning
confidence: 99%
“…inaccuracy of computing S ) without performing an intensive field campaign, where infiltration tests are combined with measurements of hydraulic parameters in the laboratory and with 2D axisymmetric modelling of the flow below the infiltrometer ( Réfloch et al, 2017 ). It is also recommended that infiltration experiments be combined with innovative non-invasive methods such as Ground Penetrating Radar, which can show the wetting front evolution with time during water infiltration ( Iwasaki et al, 2016;Klenk et al, 2015;Leger et al, 2014aLeger et al, , b, 2015Salas-García et al, 2017 ). Réfloch et al (2017) also showed that monitoring the extension of the soil moisture stain around the infiltration ring with time is valuable for deriving the horizontal and vertical hydraulic parameters.…”
Section: Future Work and Recommendations To Improve Bestmentioning
confidence: 99%
“…Governed by nonlinear physical relationships, the Richards equation is a highly nonlinear equation. The SWCC is a major factor that influences the nonlinear physical relationship of the hydraulic conductivity in unsaturated zones [19][20][21][22]. Since the Richards equation is highly nonlinear and an analytical solution can only be provided by some transformations [23], numerical solutions of the Richards equation are commonly used to model the flow process in unsaturated soils.…”
Section: Introductionmentioning
confidence: 99%
“…To compensate for this, some researchers have preferred to carry out infiltration tests in the laboratory under controlled conditions using test columns, so it is possible to measure not only the inflows, but also the outflows as well as others parameters such as water content, temperature, etc. [18,19].…”
Section: Introductionmentioning
confidence: 99%